Parkinsonism, Intellectual Disability, and Catatonia in a Young Male With MECP2 Variant. Issue 1 (21st November 2019) - Pollini, Luca; Galosi, Serena; Nardecchia, Francesca; Musacchia, Francesco; Castello, Raffaele; Nigro, Vincenzo; Leuzzi, Vincenzo
Abstract : View Supplementary Video 1